x=300-4y-7z

z=300-2y-3x Nowtake your solution for x and plug it into the expression you have for z to get: z = 300- 2y - 3(300 - 4y - 7z)

Solve that for z. Now plug that z into the expression you have forx. That will give you x = f(y) and z = g(y). Plug thoseinto the profit equation and it will now be only in terms ofy. Maximization should be easy from there.

z=300-2y-3x Nowtake your solution for x and plug it into the expression you have for z to get: z = 300- 2y - 3(300 - 4y - 7z)

Solve that for z. Now plug that z into the expression you have forx. That will give you x = f(y) and z = g(y). Plug thoseinto the profit equation and it will now be only in terms ofy. Maximization should be easy from there.